2024
DOI: 10.1039/d3ay01523h
|View full text |Cite
|
Sign up to set email alerts
|

Current methods for the detection of glypican-3

Xiangyan Xiao,
Qiyuan Huang,
Xiaocong Lin
et al.

Abstract: Lipid membrane structure of GPC3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…However, because of the deficiency of the clinical analysis method of GPC3, it is very important to detect GPC3 accurately and sensitively for the diagnosis of liver cancer. Recently, new high-sensitivity GPC3 detection technologies based on a variety of optical sensors or electro-chemical technologies have been developed, providing new perspectives for the challenges and future development of the field and also contributing to the early detection of liver cancer[ 16 , 66 , 67 ]. For HCC, the discovery of GPC3 as a promising tumor-associated antigen because GPC3 is over-expressed in cancerous tissues and is significantly associated with poor prognostic disease-free survival and overall survival[ 67 , 68 ].…”
Section: Hepatic Gpc3 Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the deficiency of the clinical analysis method of GPC3, it is very important to detect GPC3 accurately and sensitively for the diagnosis of liver cancer. Recently, new high-sensitivity GPC3 detection technologies based on a variety of optical sensors or electro-chemical technologies have been developed, providing new perspectives for the challenges and future development of the field and also contributing to the early detection of liver cancer[ 16 , 66 , 67 ]. For HCC, the discovery of GPC3 as a promising tumor-associated antigen because GPC3 is over-expressed in cancerous tissues and is significantly associated with poor prognostic disease-free survival and overall survival[ 67 , 68 ].…”
Section: Hepatic Gpc3 Signallingmentioning
confidence: 99%
“…Recently, new high-sensitivity GPC3 detection technologies based on a variety of optical sensors or electro-chemical technologies have been developed, providing new perspectives for the challenges and future development of the field and also contributing to the early detection of liver cancer[ 16 , 66 , 67 ]. For HCC, the discovery of GPC3 as a promising tumor-associated antigen because GPC3 is over-expressed in cancerous tissues and is significantly associated with poor prognostic disease-free survival and overall survival[ 67 , 68 ]. Indeed, clinical and basic studies have demonstrated that GPC3 is a carcino- embryonic proteoglycan anchored to the membrane of HCC cells and is involved in promoting HCC growth and invasion through a variety of signaling cascades; including the Wnt pathway, which plays a well-known role in embryogenesis[ 69 , 70 ].…”
Section: Hepatic Gpc3 Signallingmentioning
confidence: 99%